Grappling with the Climate Crisis in IR : Existentially, Psychologically, Interdisciplinarily - Krickel-Choi, Nina C. ; 0000-0001-5378-9744 (Czech Journal of International Relations, 2025)
The introduction to this special issue argues that International Relations (IR) needs to give greater consideration to the existential and psychological implications of the accelerating climate crisis. Starting from debates about the disciplinary suitability of IR to meaningfully tackle an issue as all-encompassing as climate change, this introduction gives a short overview of how the problem of climate change has conventionally been conceived, and finds that IR has so far not sufficiently appreciated the psychological implications of the climate crisis. Yet, such a perspective is sorely needed, as climate change is not only an environmental problem but also a problem of existentialist sense-making, and because IR’s actors are themselves deeply affected by changes to the physical world that they are a part of. Consequently, this introduction provides a sketch of what an existential-psychological inquiry into the implications of climate change could look like and concludes that, regardless of the current state of the discipline, IR has a duty to become a discipline that can meaningfully contribute towards mitigating the climate crisis.
Keywords: climate change; existentialism; interdisciplinarity; IR; psychology